Simplification of administrative procedure on the example of the Czech Republic, Poland, Slovakia, and Hungary (V4 countries) - Lukáš Potěšil; Krisztina Rozsnyai; Jan Olszanowski; Matej Horvat (Administrative Sciences, 2021)
The article deals with the idea of simplification of administrative procedure on the example of legal regulation that can be found in Poland, Slovakia, the Czech Republic, and Hungary. This legal regulation comes from the same or similar evolution and legal conditions. General legal regulation of administrative procedure is represented by so called Code of Administrative Procedure. Existence of such code in all mentioned countries might be regarded as a first step towards simplification. Using research methods-dogmatic, normative, and, namely, comparative-the article examines concrete examples of simplification in mentioned countries that have similar approaches in solving this demand. This article mentions possible views (or addressees) on the need of simplifications as well as possible limits of this issue. In this sense, the protection of the public interest and protection of rights of individuals presents certain limitations to simplification. Legal regulation of administrative procedure is complicated. Although each legal regulation is in detail specific, we can find some common solutions in particular legal regulation of simplifications. Such results of this article might be useful (not only) for further comparison in European countries.
Keywords: 350; administrative procedure; code of administrative procedure; simplifications; V4 countries; Poland; Slovakia; the Czech Republic; Hungary